Major congenital malformations of foetus: a bane in pregnancy - Christe, D. M.; Mohana, D.; Shobha, S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: The aim of the study was to find out the numbers of women presenting with pregnancy complicating with major congenital anomalies of the fetus. Methods: This study was conducted over a period of fifteen months in the year 2018-2019. The types of congenital anomalies were that of the central nervous system, cardiac, renal, gastrointestinal, skeleto-muscular, hydrops foetalis, chromosomal, single umbilical artery and other multiple anomalies. Other variables regarding the age group of the mother, gravida, parity and gestational age at which the pregnancy was terminated was also noted. Results: A total of 212 pregnancies were diagnosed with major congenital anomalies of fetus and opted for termination. Malformations of the central nervous system (CNS) of fetus, formed the largest group of 56.6%, and fetal gastrointestinal malformations and fetal renal anomalies occupied the second major groups forming 11.8% and 11.3% respectively. The age group of women ranged between 23 years to 38 years. The largest group of pregnant women with fetal malformations were aged between 23-27 years. Primigravida with zero parity women were 60.4% of the total group of women with major fetal anomalies. Conclusions: Maximum number of congenital anomalies were seen in primigravida and para one mothers. Genetic counseling should be offered for women at clinics, before planning further pregnancy. Facilities should be made available for poor people from remote areas for early detection of congenital anomalies.